UPAYA GURU TAHFIDZ DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR’AN - Linda Evy Oktaviani; Imam Suhadi; Yetty Faridatul Ulfah (Raudhah - Proud To Be Professional, 2023)
The purpose of this study is 1) To determine the efforts of tahfidz teachers in improving students' Qur'an memorization skills, 2) To find out the supporting and inhibiting factors faced by tahfidz teachers in improving the ability to memorize the Qur'an in grade VII students of SMP Muhammadiyah Imam Syuhodo. In this study, researchers used qualitative methods with a descriptive approach. The results of research on the efforts of tahfidz teachers in improving the ability to memorize the Qur'an in grade VII students of SMP Muhammadiyah Imam Syuhodo are as follows: 1) Targeting student memorization, giving consequences and rewards to students. The supporting factors in improving students' memorization of the Qur'an, namely: 2) The use of Qur'an blocks to make it easier for students to memorize, habituation to students to listen to the Qur'an murottal every morning, accustom students to muroja'ah together in the morning before the start of KBM and in the afternoon before school, holding tahsin lessons for all students, increasing tahfidz teachers. As for the inhibiting factors, among others: The decline in students' enthusiasm to memorize the Qur'an, the ability or intelligence of different students, still not fluent in reading the Qur'an students, and students still find it difficult to pronounce makhorijul letters.